The impact of knowledge management practices on the acceptance of Massive Open Online Courses (MOOCs) by engineering students: A cross-cultural comparison. (November 2020) - Arpaci, Ibrahim; Al-Emran, Mostafa; Al-Sharafi, Mohammed A.
Highlights: The impact of KM practices on the acceptance of MOOCs was investigated. KM practices have a positive and significant impact on the PU. PEOU has a positive and significant impact on knowledge sharing. There was a difference in acceptance behavior between Malaysia and Turkey. Abstract: This study conducted a cross-cultural analysis of the impact of knowledge management (KM) practices on the acceptance of Massive Open Online Courses (MOOCs). The study extended the Technology Acceptance Model (TAM) with KM practices. A structural equation modeling (SEM) was employed to test the hypothesized relationships based on data collected from 540 engineering students in Malaysia and Turkey. The results indicated that KM practices, including knowledge access, knowledge storage, and knowledge application have a positive and significant impact on perceived usefulness (PU) of MOOCs. However, knowledge sharing has a positive and significant impact on perceived ease of use (PEOU) of MOOCs. Further, a SEM-based multi-group analysis was employed to identify the moderating role of culture in examining the impact of KM practices on MOOCs acceptance. The findings suggested cultural differences in patterns between acceptance behaviors of engineering students in Malaysia and Turkey.